Reduction of mineral fertilization of Arabic coffee using coffee straw - Fernandes, André Luís Teixeira; Santinato, Felipe; Ticle, Rodrigo; Santinato, Roberto (Coffee Science - ISSN 1984-3909, 2014)
This study, conducted in Araxá, MG, aimed to evaluate the technical feasibility of reducing the levels of nitrogen, phosphorus, potassium and sulfur recommended for the mineral nutrition of arabic coffee using coffee straw as organic matter in increasing doses (2,5; 5,0; 10,0 e 20,0 t ha-1) added to the mineral fertilizer recommendations, reducing proportionately the quantities of nutrients in the straw. After three seasons (2008 to 2010), the conclusions were that: a) it is feasible to use coffee straw as a source of N, P, K and S with consequent reduction of mineral fertilizer nutrients in coffee, for it allows increase in productivity up to 25%; b) mineral fertilizers, both exclusive and with the reduced coffee straw are significantly higher in yield (88-135%) to the control, demonstrating the need for these nutrients in coffee cultivation in conditions of cerrado; c) the doses of coffee straw does not change the pH, V%, Ca+2, Mg+2, increase K+ and B, and Mg+2, which remained with suitable levels and tended to increase CTC and organic matter, while reducing the Cu; d) the levels of N, P and K fertilizer can be reduced: from 6 to 44% for N, 8 to 54% for P; 28 to 100% for the K and from 8 to 68% for the S with the use of straw as organic fertilizer for coffee crop.